2019
DOI: 10.1016/j.lwt.2018.05.013
|View full text |Cite
|
Sign up to set email alerts
|

Enzymatic modification of grapeseed (Vitis vinifera L.) oil aiming to obtain dietary triacylglycerols in a batch reactor

Abstract: Structured lipids (SL) are chemically or enzymatically modified oils and fats with respect to their original fatty acid composition or position in acylglycerols. These compounds present improved functional or nutraceutical properties. The present work aimed at the enzymatic synthesis of SL, MLM-type dietary triacylglycerols, that is, those with medium chain fatty acids (M) at the sn-1 and sn-3 positions, and long chain fatty acids (L), in the internal position of the triacylglycerol. Grapeseed oil was selected… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
31
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
8
1

Relationship

3
6

Authors

Journals

citations
Cited by 35 publications
(37 citation statements)
references
References 33 publications
(38 reference statements)
3
31
0
Order By: Relevance
“…Yet, it is possible to identify the region corresponding to the best results (T = 64-66 • C; MR = 4-5:1). In the acidolysis reaction between C8:0 or C10:0 and grapeseed oil, in the solvent-free system, using the same immobilized commercial lipases, Bassan et al [19] reported an optimal temperature of 69 • C in the reaction system, also found by Response Surface Methodology, which was very close to the optimal temperature observed in this study (Figure 3). Additionally, the best results were reported for C10:0 as medium-chain fatty acid and Lipozyme RM IM lipase as a catalyst.…”
Section: Modelling Acidolysis and Optimization Of Reaction Conditionssupporting
confidence: 86%
See 1 more Smart Citation
“…Yet, it is possible to identify the region corresponding to the best results (T = 64-66 • C; MR = 4-5:1). In the acidolysis reaction between C8:0 or C10:0 and grapeseed oil, in the solvent-free system, using the same immobilized commercial lipases, Bassan et al [19] reported an optimal temperature of 69 • C in the reaction system, also found by Response Surface Methodology, which was very close to the optimal temperature observed in this study (Figure 3). Additionally, the best results were reported for C10:0 as medium-chain fatty acid and Lipozyme RM IM lipase as a catalyst.…”
Section: Modelling Acidolysis and Optimization Of Reaction Conditionssupporting
confidence: 86%
“…MLM structured lipids are currently synthesized by acidolysis reaction between an oil rich in long-chain FA (e.g., olive, olive pomace, linseed, spent coffee grains, grapeseed, avocado, or microbial oils) and medium-chain FA, namely octanoic (C8:0; common namecaprylic acid) or decanoic (C10:0; common name-capric acid) acids, catalyzed by sn-1,3regioselective lipases [10,12,13,[16][17][18][19][20][21][22][23][24].…”
Section: Introductionmentioning
confidence: 99%
“…For example, Lipozyme TL-IM, Lipozyme RM-IM and N435 were compared in the synthesis of caprylic or capric acids/long chain fatty acids/caprylic or capric acid triglycerides via batch acidolysis in solvent-free medium. 452 As an oil substrate, grapeseed oil (rich in linoleic acid) was utilized. The best results were obtained using capric acid and Lipozyme RM-IM.…”
Section: View Article Onlinementioning
confidence: 99%
“…When applying immobilized enzymes for the industrial production of SLs, several factors have to be considered to fulfill their catalytic potential and maximize the acquisition of the target products. First, for a specific SL, it is required to screen the desired immobilized lipase and determine the optimal processing conditions (for example, substrate ratio, enzyme amount, reaction temperature, time, and pH) (Bassan et al., ; He et al., ; Wang, Wang, Wang, Jin, & Wang, ). Second, it is also important to select suitable reactors.…”
Section: Synthesis Of Slsmentioning
confidence: 99%